Influence of STEM Approach for English Language Teaching and Learning - Ogechukwu Mary Nwanna; Oluchukwu Ann Anueyiagu (Educare: Journal Educational and Multimedia, 2025)
With the recent digitalization across the globe, there is virtually no sector of education without the emergence/ usage of technology. Science, technology, engineering and mathematics (STEM) have no doubt turn the world of education into a cozy environment. STEM education has proven to be an avenue in different fields for creativity, critical thinking, problem-solving and also increases academic achievement and retention of what is; of which Language learning is not exempted. Language learning and STEM education are synonymous in the sense that the use of technological approach in Language laboratory has proven that it makes learning of Language for students easier, more accessible and more retentive. Language teachers have been benefitted from the use of technological approach in diverse ways ranging from wed seminar, zoom teachings and online conferences. This systematic review analyzed peer-reviewed studies (2013–2023) on STEM integration in English language teaching, sourced from major databases. Using thematic analysis, it synthesized evidence on technological tools, pedagogical strategies, learner outcomes, and teacher capacity building. Findings from the study revealed that STEM approach and Language learning are undeniable fact. The influence of STEM approach on Language learning makes learning of Language effective and efficient for both the Language teachers and the students. Based on the findings, the following recommendations were made that government and other stakeholders should make STEM education an upskill venture and compulsory for teaching of language in our schools.